Effect of the Vitamin E on Expression of Apoptosis-Related Proteins in Immobilized Rat Testes - Kukner, Aysel; Oner, Jale; Oner, Hakan; Ozan, Enver (Medwell Online, 2010)
The aim of this study was to investigate effect of the vitamin E on changes in Bax and Bcl-2 expression in the rat testes during immobilisation stress. The animals were divided into three groups. The rats in group I were immobilised for 6 h on 5 consecutive days. The rats in group 11 were daily injected vitamin E (100 mg kg(-1)) for 5 days during immobilisation. Control rats were allowed to move freely. The percentage of Bax immunpositive spermatogonia in stress group was significantly higher than those in control groups (p<0.05) but Bcl-2 was not significantly (p>0.05.). The percentages of Bax and Bcl-2 immunpositive cells in the vitamin E treated group was decreased than the immobilization stress group. It was observed that Bax and Bcl-2 expression were peak level (+) in the spermatogonia of the control group. In this group, Bax and Bcl-2 expression were not determined mostly in the seminifer tubules. Neither Sertoli cells nor spermatids showed immunoreaction. Bax immunoreactivity was observed at strong level (+++) in both spermatogonia and intersititial cells of immobilised rats. In this group, Bcl-2 protein was expressed at peak level (+) in the spermatogonia. Bax expression was decreased in vitamin E treated group and at peak level (+) immunreaction was showed in the spermatogonia and intersitisyal cells. Findings of this study show that the immobilisation stress increases apoptosis and vitamin E decreases Bax and Bcl-2 expression that are apoptosis-releated proteins in the immobilised rat testes.
Keywords: Bax; Bcl-2; immobilisation; testes; vitamin E; spermatogonia